Immediate effect of thoracic manual therapy on respiratory parameters, chest expansion and rom of thorax and cervical spine in mild to moderate COPD-A randomized clinical trial - Ganesh BR; Chandra Bahadur Khatri (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Background: COPD is one of the non-communicable diseases related to lung parenchyma and airways which are one of the leading causes of death and disability in India. COPD is not only considered as lung disease but also it has systematic effects that lead to co-morbidities contributing to poor performance in functional level and decreased quality of life. COPD has considerable effects in musculoskeletal system. It ranges from muscle dysfunction of respiratory system to skeletal muscle system to reduced bone density. It is also associated with decreased range of motion in cervical and thoracic region. Physiotherapy plays vital role in preventing and managing the complications in COPD patients. It has been long since exercises that consists of breathing techniques, thoracic expansion exercise and techniques to clear the secretion has been used for management of COPD. One of the emerging techniques for management of musculoskeletal dysfunctions is manual therapy. Hence current study is intended to compare the acute effects of breathing exercises and thoracic expansion exercises with high velocity low amplitude thrust. Objectives: To evaluate and compare the immediate effect of High velocity low amplitude thrust with breathing exercises and thoracic expansion exercises on respiratory parameters, chest mobility and range of motion in cervical and thoracic spine. Methods: Total 26 participants were divided randomly into HVLAT group (N=13) and exercise group (N=13). All the participants were assessed for baseline outcome measures and received respective treatment. Following treatment, the pulmonary function test, thoracolumbar flexibility, cervical range of motion and chest expansion were recorded and analysed. Results: Mean age of participants in HVLAT group was 60.08±5.31 years and exercise group was 60.23±4.60 years and both groups were homogeneous in nature. Significant differences were observed only in thoracolumbar flexibility within both groups (p=0.001), increased cervical flexion (p=0.026) and chest expansion at axillary level (p=0.026) in exercise group and increased lateral flexion in HVLAT group (p=0.044) but there were no any differences in other parameters within and between two groups. Conclusion: This study concluded that either of the intervention was insufficient to produce significant effects on respiratory parameters, range of motion and chest expansion except for thoracolumbar flexibility, cervical flexion and lateral flexion. Neither of treatment is superior to one another in terms of their acute effects.